O novo sistema de geração e aquisição de agitação marítima do laboratório de hidráulica da FEUP - Francisco Taveira Pinto (2007)
The Hydraulics Laboratory of the Faculty of Engineering University of Porto (FEUP) has been recently reequipped (May 2007, with funds from the Project: Financiamento Programático CEHRA1) with a Multi-Element Wave Generation System incorporating Dynamic Wave Absorption (HR Wallingford, UK), which allows the simulation of several kinds of 2D and 3D sea wave states. This way, the wave basin acquired extended capabilities for a wider range of physical modelling applications in Port and Coastal Engineering studies, namely for research, education and to support other projects. The system has already been tested, being presently operational and in use. In this paper, the system specifications and description is presented together with the processes of wave generation, hydrodynamic probes calibration and wave data acquisition and analysis. Furthermore, application examples, namely, concluded studies as well as undergoing and planned works are also pointed out. In addition a brief historical review of Hydraulics Laboratory will be performed.